Radical prescription : citizenship and the politics of tuberculosis in twentieth-century Cuba - Urban, Kelly (Envisioning Cuba., 2023)
"In this first comprehensive study of tuberculosis in modern Cuba, Kelly Urban analyzes the medical, social, and governmental responses to the highly contagious disease, particularly as the island was heading into and emerging from the 1959 revolution. Tuberculosis--one of the top three causes of death in Cuba at the beginning of the twentieth century--provides a window onto broad questions of citizens' rights, biomedicine and public health, and political change"--